Good faith in implementing the contract - Sulaiman, Sherzad Aziz; Ali, Yonis Othman (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The principle of good faith is one of the main principles in civil laws, and good faith requires honesty, sincerity and cooperation in implementing the obligations of the parties to the contract, and it is a basic principle in all stages of the contract and in particular the stage of contract implementation as its presence in the implementation phase guarantees all the contractors access to the benefit Desired contract. The positions of the comparative legislations vary in the text of this principle, but what is worth noting is that the Iraqi and Egyptian laws have explicitly stipulated this principle at the stage of implementing the contract, while the position of the French legislator after the 2016 amendments to the civil law was more clear by stating that it must be good The intention is present in all stages of the contract, starting with the conclusion stage until the implementation of the contract. There are several obligations that derive from this principle, including the obligation to exercise caution and seriousness in the implementation of the obligation, the commitment to honesty and sincerity in the implementation of the contract and the duty of the creditor to facilitate implementation and inform the debtor of the circumstances that affect the progress of implementation, in addition to the above, there are different functions for this principle in contracts, which leads to mitigation From the severity of the literal implementation of agreements, as well as the observance of good faith in implementation limits annulment, and that resorting to good faith leads to a reduction in cases of breach of contract.